Comparison of Health Examination Survey Methods in Brazil, Chile, Colombia, Mexico, England, Scotland, and the United States. Issue 6 (21st August 2017) - Mindell, Jennifer S.; Moody, Alison; Vecino-Ortiz, Andres I.; Alfaro, Tania; Frenz, Patricia; Scholes, Shaun; Gonzalez, Silvia A.; Margozzini, Paula; de Oliveira, Cesar; Sanchez Romero, Luz Maria; Alvarado, Andres; Cabrera, Sebastián; et al.
Abstract: Comparability of population surveys across countries is key to appraising trends in population health. Achieving this requires deep understanding of the methods used in these surveys to examine the extent to which the measurements are comparable. In this study, we obtained detailed protocols of 8 nationally representative surveys from 2007–2013 from Brazil, Chile, Colombia, Mexico, the United Kingdom (England and Scotland), and the United States—countries that that differ in economic and inequity indicators. Data were collected on sampling frame, sample selection procedures, recruitment, data collection methods, content of interview and examination modules, and measurement protocols. We also assessed their adherence to the World Health Organization's "STEPwise Approach to Surveillance" framework for population health surveys. The surveys, which included half a million participants, were highly comparable on sampling methodology, survey questions, and anthropometric measurements. Heterogeneity was found for physical activity questionnaires and biological samples collection. The common age range included by the surveys was adults aged 18–64 years. The methods used in these surveys were similar enough to enable comparative analyses of the data across the 7 countries. This comparability is crucial in assessing and comparing national and subgroup population health, and to assisting the transfer of research and policy knowledge across countries.